BOOK REVIEW OF ‘ISLAMIC SOURCES AND INTERNATIONAL LAW’ - sulaiman Dorloh; Muhammad Atiullah bin Othman (AR-RĀ’IQ, 2023)
This brief review examines the new book, Islamic Sources and International Law, published in 2023 by Nova Science Publishers in New York, in the United States of America. The book, ‘Islamic Sources and International Law’ (Nehaluddin Ahmad & Gary I. Lilienthal, 2023), conducts a critical investigation of whether people are bound by international treaties, in either or both Islamic and liberal democratic traditions. It considers those countries, that identified as liberal democracies, as being the primary adherents of western-derived international law.